Adolescents' Self-Perception about Auditory Behavior: Agreement with Parents and Central Auditory Processing Evaluation - Nardez, Taina Maiza Bilinski; Guijo, Laura Mochiatti; Lucas, Priscila de Araújo; Cardoso, Ana Cláudia Vieira (International Archives of Otorhinolaryngology, 2021)
Introduction Central auditory processing disorder (CAPD) has been diagnosed through behavioral tests. Moreover, screening tools as validated questionnaires may contribute to identify individuals at risk for this disorder, including adolescents.Objective (1) to characterize and compare adolescents' self-perception regarding their auditory behavior with their parents' perception; (2) to verify their agreement with behavioral evaluation of central auditory processing (CAP).Methods Cross-sectional, prospective, and descriptive study, in which 40 adolescents and 40 parents of both genders participated. All participants answered the scale of auditory behaviors questionnaire, and the behavioral evaluation of CAP was conducted with the adolescents. Findings were analyzed descriptively and inferentially, with a significance level of 5% (p ≤ 0.05) and application of the following tests: Test for equality of two proportions, Chi-squared, and Kappa concordance index.Results Most adolescents rated their auditory behavior as “low risk” for CAPD while their parents rated it as “typical.” When comparing adolescents' self-perception and parents' perception about the auditory behavior with the behavioral evaluation outcome, a statistically significant difference was observed only in adolescents' self-perception. The results of the behavioral evaluation indicated that 42.5% of the adolescents showed alterations. The concordance index between adolescents' self-perception and parents' perception of auditory behavior showed a significant (minimal) difference.Conclusion Most adolescents were able to perceive difficulties regarding their auditory behavior and characterized it as “low risk” for CAPD, but the same did not occur regarding their parents. There was agreement only between the adolescents' self-perception and their performance in the behavioral evaluation of CAP.
Keywords: hearing; auditory tests; auditory perception; adolescents